Microfinance banking : principles and practice - Agene, Casmir Emman (Abuja, Nigeria : Gene Publications, 2011)
The book explains the scope and nature of microfinance business as well as the operation methodology of microfinance banks in Nigeria.
Includes bibliographical references and index.
oif 29/07/2020
Loans
Keywords: Microfinance; Nigeria